2022
DOI: 10.2478/rir-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT pathway targeting in primary Sjögren syndrome

Abstract: Primary Sjögren's syndrome (pSS) is an autoimmune systemic disease mainly affecting exocrine glands and resulting in disabling symptoms, as dry eye and dry mouth. Mechanisms underlying pSS pathogenesis are intricate, involving multiplanar and, at the same time, interlinked levels, e.g., genetic predisposition, epigenetic modifications and the dysregulation of both immune system and glandular-resident cellular pathways, mainly salivary gland epithelial cells. Unravelling the biological and molecular complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…The pro-inflammatory cytokine IL-6 was shown to be increased in the biological fluids of pSS patients and mediate its pathogenesis through the modulation of B and T cell differentiation and activation. Similarly, IL-21 and IL-23 are involved in the activation of B cells as well as in the generation of IL-17-secreting T cells (Th17 cells) [ 37 ]. IL-23 is also involved in the expansion of innate lymphoid cells (ILC), which mainly produce IL-17, thus enhancing the vicious cycle of inflammation.…”
Section: Pathogenesismentioning
confidence: 99%
“…The pro-inflammatory cytokine IL-6 was shown to be increased in the biological fluids of pSS patients and mediate its pathogenesis through the modulation of B and T cell differentiation and activation. Similarly, IL-21 and IL-23 are involved in the activation of B cells as well as in the generation of IL-17-secreting T cells (Th17 cells) [ 37 ]. IL-23 is also involved in the expansion of innate lymphoid cells (ILC), which mainly produce IL-17, thus enhancing the vicious cycle of inflammation.…”
Section: Pathogenesismentioning
confidence: 99%
“…[107][108][109][110][111][112][113][114][115] Due to the important role of JAK-STAT pathway in the pathogenesis of pSS and the success of Jakinibs for the treatment of RA and SLE, Jakinibs seem to be promising therapies for pSS patients. [101,116] At the cell level, JAK1/2 inhibitors can suppress JAK-STAT pathway activated by IFNa/g or H 2 O 2 . This suppression subsequently inhibits downstream effects, including the increase in aberrant DNA epigenetic reprograming, [77] high expression of tissue-type plasminogen activator, [97] and CXCL10 expression.…”
Section: Stat5mentioning
confidence: 99%
“…Though a recent phase-2b clinical trial of ianalumab (VAY736) reported efficacy, clinical trials of other biologic DMARDs (e.g., rituximab, belimumab, and abatacept) had conflicting clinical results in pSS patients [107–115] . Due to the important role of JAK-STAT pathway in the pathogenesis of pSS and the success of Jakinibs for the treatment of RA and SLE, Jakinibs seem to be promising therapies for pSS patients [101,116] . At the cell level, JAK1/2 inhibitors can suppress JAK-STAT pathway activated by IFNα/γ or H 2 O 2 .…”
Section: Role Of Jak-stat Signaling Pathway In Treatment Of Pssmentioning
confidence: 99%
“…Many of the inflammatory cytokines implicated in SjD pathogenesis, in particular type-I and type-II interferons (IFNs), interleukins (IL)-6, IL-7, IL-12 and IL-21, signal through the Janus kinases (JAKs)–signal transducer and activator of transcription (STAT) pathway 12. Previous reports have tried to investigate the role of IFN signalling and involvement of JAK-STAT pathway in SjD using various organoids and mouse models13–16; however, a comprehensive understanding of this pathway in SjD patients’ tissues using multimodal methodologies is still required.…”
Section: Introductionmentioning
confidence: 99%